Monoclonal antibody-based icELISA for the screening of diazinon in vegetable samples. Issue 16 (31st March 2021) - Wu, Hui-Ling; Wang, Bing-Zhi; Wang, Yu; Xiao, Zhi-Li; Luo, Lin; Chen, Zi-Jian; Shen, Yu-Dong; Xu, Zhen-Lin
Abstract : Diazinon (DAZ) is an organophosphorus pesticide (OP), which is commonly used to prevent and control harmful pests that endanger agricultural products. Abstract : Diazinon (DAZ) is an organophosphorus pesticide (OP), which is commonly used to prevent and control harmful pests that endanger agricultural products. In this study, we developed a novel heterology coating strategy for the immunoassay of DAZ. The DAZ coating hapten can be directly conjugated to the carrier protein without requiring a spacer arm. This proposed hapten coating strategy is time-saving and significantly improves the sensitivity of the immunoassay due to the lack of a spacer arm. The as-synthesized coating antigen was used to screen the monoclonal antibody (mAb). Finally, the developed indirect competitive enzyme-linked immunoassay (icELISA) showed IC50 and limit of detection (LOD) values of 0.58 ng mL −1 and 8 pg mL −1, respectively. This method exhibited negligible cross-reactivity towards other analogues, and the recoveries of samples (cucumber, cabbage, and lettuce) ranged from 92.6% to 125.4%, with coefficients of variance (CV) below 12%. Good correlation between icELISA and high-performance liquid chromatography mass spectrometry (HPLC-MS/MS) was obtained. The proposed icELISA was an ideal tool for monitoring DAZ residues in food samples.